099 High relapse rate with steroid monotherapy in non-systemic vasculitic neuropathy. Issue 6 (27th May 2022) - Bunting, Eva; Cooper, Rebecca; Seral, M; Manji, H; Rossor, A; Reilly, MM; Lunn, MP; Bennett, D; Hadden, R; Carr, AS
Abstract : Introduction: Historically, single tissue vasculitis has been managed with steroid monotherapy. Recent data from large longitudinal databases on systemic vasculitis suggest Non-Systemic Vasculitic Neuropathy (NSVN) has higher rates of relapse, recommending that more aggressive immunotherapy is employed. Aim: To investigate the relapse rate in NSVN in response to steroid monotherapy. Methods: A retrospective case note review of clinically and/or pathologically defined cases of (Systemic Vasculitic Neuropathy) SVN and NSVN in two London specialist peripheral nerve centres, between 2005 - 2012 and 2015 - 2019. Results: 32 cases of SVN and 34 cases of NSVN were identified. In each group 14 individuals were treated first-line with steroid monotherapy, and 8 with cyclophosphamide. 8 SVN and 9 NSVN cases received steroids plus azathioprine. 15/32 SVN and 13/34 NSVN relapsed after first-line therapy (10/14 and 9/14 on steroid monotherapy, 3/8 and 3/9 on steroids and azathioprine, 2/8 and 1/8 on cyclophosphamide). 10 individuals stabilised with the addition of azathioprine, 13 with cyclophosphamide and 4 with Rituximab. Conclusion: This representative case series suggests that steroid monotherapy is inadequate in the treatment of NSVN and supports an approach akin to that recommended in SVN, even if nerve is the only tissue clinically involved. e.bunting@nhs.net